Lithic raw material acquisition and use by early Homo sapiens at Skhul, Israel. Issue 127 (February 2019) - Ekshtain, Ravid; Tryon, Christian A.
Abstract: The site of Skhul in Israel has featured prominently in discussions about the early presence of Homo sapiens outside of Africa since its excavation in the 1930s. Until now, attention has been primarily focused on the site's fossil hominins and evidence for symbolic behavior in the form of burials and rare artifacts such as pierced shells and pigment objects. We present here the results of renewed analysis of the lithic artifacts from Skhul drawn from archival collections in the United States, United Kingdom, and Israel. Although lithic artifacts form the majority of the archaeological record from the site, they have rarely been the subject of comprehensive study. Our analyses of raw material selection, use and transport combined with technological analyses of artifact production methods (1) indicate selective transport to the site of large flakes, retouched pieces, and particularly Levallois points from non-local sources, and (2) demonstrate substantial variability in raw material procurement that fails to indicate clear differences in landscape use between H. sapiens and Neanderthals.